Defining the decision problem: a scoping review of economic evaluations for Clostridioides difficile interventions. (March 2022) - Richardson, M.; Erman, A.; Daneman, N.; Miller, F.A.; Sander, B.
Summary: Background: Clostridioides difficile infection is the leading cause of healthcare-associated infectious diarrhoea. Several preventative and treatment interventions exist; however, decisions for their use are typically made independent of other interventions along the care pathway. Aim: To assess how the scope of the decision problem is defined in economic evaluations of C. difficile interventions. Methods: A scoping review was conducted following the Joanna Briggs Institute framework using a comprehensive literature search with C. difficile and economic evaluation as key search concepts. Study selection and extraction were performed independently by two reviewers. An in-depth analysis of all cost-utility and cost-effectiveness analyses was conducted. Care pathway domains (i.e. infection prevention and control, antimicrobial stewardship programmes, prevention, diagnostics, treatment) were defined iteratively, and each study was classified according to the scope of the decision problem: (i) one intervention, one domain; (ii) one intervention, multiple domains; (iii) multiple interventions, one domain; and (iv) multiple interventions, multiple domains. Results: In total, 3886 studies were identified. Of these, 116 studies were included in the descriptive overview, and 46 were included in the in-depth analysis. Most studies limited the scope of the decision problem to one intervention (43/46; 93%). Only three studies (3/46; 7%) assessed multiple interventions – either as bundled vs standalone interventions for prevention (i.e. a single domain), or as sequences of treatments for initial and recurrent infection (i.e. multiple domains). No study assessed multiple interventions across prevention and treatment domains. Conclusions: Economic evaluations for C. difficile infection assess narrowly defined decision problems which may have implications for optimal healthcare resource allocation.